Pengaruh Kepemimpinan daan Iklim Organisasi Terhadap Kinerja Karyawan di Four Points By Sheraton Bali Seminyak - Peter Valdez Alan Ulimpa; Ni Made Ariani; Ni Putu Ratna Sari (Jurnal Kepariwisataan dan Hospitalitas, 2022)
Abstract One of the most important in organizations or companies, where human resource management is the activity of getting the right people in the organizational climate. However, there are many factors that influence the performance of employees when they work, some of which are the superior leadership style and organizational climate adopted by each company. This study aims to determine the influence of leadership and organizational climate simultaneously and partially at Four Points by Sheraton Bali Seminyak and also to determine the most dominant influencing variables. Respondents in this study were permanent and contract employees at Four Points by Sheraton Bali, Seminyak who were taken by 75% of the total employees so that 100 employees were obtained. Respondents were stratified using proportional stratified random sampling. The data analysis technique used validity test, reliability test, classical assumption test, correlation analysis, multiple linear analysis and hypothesis testing using the F test and t test and the test of determination. The results showed a positive and significant relationship simultaneously between leadership and organizational climate on employee performance. This is evidenced by the calculated F value (142.584) greater than F table (3.09). Partially the leadership variable has a positive and significant effect with the t value (2.256) greater than the t table (1.984). The organizational climate variable also has a positive and significant effect with the t value (10.777) greater than the t table (1.984). The results of termination show that leadership and organizational climate have an effect of 74.6% on employee performance. The dominant variable which influences is organizational climate. This is evidenced by the beta standard coeficients value of organizational climate (0.610) is greater than leadership (0.153). Keywords: leadership, organizational climate, Four Points by Sheraton Bali Seminyak